EFL students’ efficacy and anxiety in speaking English - Fatayatul Hanani Safrul; Habiburrahim Habiburrahim; Janice Orrell; Zamzami Zainuddin; Muhammad Safwan Safrul (Englisia: Journal of Language, Education, and Humanities, 2026)
ABSTRACT - The ability to speak English confidently remains a major challenge for many learners in English as a Foreign Language (EFL) context. While previous research has established links between speaking anxiety and self-efficacy, less attention has been given to how learners interpret their own accents and how these perceptions influence their willingness to communicate. This qualitative study explores the experiences of eight Acehnese EFL university students in relation to speaking self-efficacy, foreign language anxiety, accentedness, and intelligibility. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that participants differed considerably in how they defined successful spoken communication. Some regarded intelligibility and mutual understanding as the primary goals of speaking, whereas others associated successful communication with achieving a native-like accent. For many participants, fear of negative evaluation emerged as a significant source of anxiety, leading to avoidance of speaking opportunities and reduced confidence. The study also found that the pursuit of native-like pronunciation was often linked to broader concerns about social recognition, legitimacy, and status rather than communication alone. In addition, inconsistencies between teachers’ stated emphasis on intelligibility and the continued use of native-speaker models contributed to uncertainty and heightened anxiety among learners. The findings suggest that speaking self-efficacy is shaped not only by linguistic competence but also by learners’ perceptions of how their speech is evaluated by others. The study highlights the importance of creating classroom environments that value intelligibility, acknowledge linguistic diversity, and support learners in developing confidence as legitimate English users. Such approaches may help reduce anxiety and encourage more active participation in spoken communication.